Determinan Variabel Makroekonomi terhadap Indeks Saham Syariah Indonesia - Sari, Linda; Asngari, Imam; Yunisvita (Jurnal Informatika Ekonomi Bisnis, 2025)
This study analyzes the influence of macroeconomic variable determinants, namely inflation, exchange rates, profit-sharing, and economic growth, on the Indonesia Sharia Stock Index (ISSI). Using the Error Correction Model (ECM) method, this research identifies both short-term and long-term relationships between these variables. Data were obtained from the Financial Services Authority (OJK), the Indonesia Stock Exchange (BEI), and the Central Statistics Agency (BPS) during the period of 2012–2022. The results indicate that exchange rates and economic growth have a significant impact on the ISSI in both the short and long term. However, inflation does not show a significant effect in either time frame. This study provides important implications for investors and policymakers in understanding the dynamics of the sharia capital market in Indonesia.